Sex and reproductive stage differences in the growth, metabolism, feed, fecal production, excretion and energy budget of the Amazon River prawn (Macrobrachium amazonicum) - Augusto, Alessandra [UNESP]; Masui, Douglas Chodi (Taylor & Francis Ltd, 2014)
The aim of this study was to evaluate differences in various physiological measures (growth, fecal production, feed intake, nitrogenous excretion, oxygen consumption, energy substrate used, and energy budget) among males, ovigerous females and non-ovigerous females of the freshwater prawn Macrobrachium amazonicum. This species exhibits pronounced sexual dimorphism and different male morphotypes and has the potential for use in aquaculture. Males and non-ovigerous females were studied for 30 days. Ovigerous females were studied for 10 days. Prawns were fed commercial prawn food, and all males were of the Translucent Claw (TC) morphotype. The results demonstrate physiological differences both between males and females and between females of different reproductive stages. Males had higher rates of ingestion, growth and oxygen consumption and less fecal loss than females. We postulate that in the absence of other morphotypes, TC males may exhibit increased growth rates. Males and females used protein as an energy substrate. Males channeled approximately 9% of their energy budget into growth, whereas non-ovigerous and ovigerous females channeled only 1.4 +/- 0.4 and 0.07 +/- 0.07%, respectively. Whereas males and non-ovigerous females channeled 9.0 +/- 9.74 and 61.8 +/- 3.0%, respectively, of the energy ingested into metabolism, ovigerous females channeled 97.7 +/- 4.7% into metabolism, likely due to the frequent beating of their pleopods, which oxygenates and cleans the eggs. As reported for marine prawns, males and non-ovigerous females of M. amazonicum lost approximately 5% of their ingested energy in exuviae. The physiological differences observed between the sexes and between females of different reproductive stages might reflect corresponding differences in patterns of activity, growth, and reproduction.
Keywords: crustacean; prawn; Macrobrachium amazonicum; physiology; sex differences; metabolism; excretion; oxygen consumption